WATER AS THE CAUSE OF ARMED CONFLICTS IN THE 21ST CENTURY - Paweł Borek (Rozprawy Społeczne)
The modern war for raw materials has a cross-border character, especially due to state borders being less than sealed tight, as well as due to the varied nature of such conflict types. The main cause of this state of affairs stems from the impact exerted on the outbreak and proliferation of resource-related conflicts by a steadily increasing worldwide demand for natural resources. An important role in the emergence of conflict situations is played by the fact that most of the resources which are on offer can be found in both politically and economically unstable countries. Water is a basic natural resource, an integral element of all social and ecological activities, used, among others, for the production of energy, food, maintaining human health or industrial development. In the twenty-first century, water systems and water supply systems are becoming increasingly vulnerable to attacks during hostilities, as well as prone to causing armed conflicts with the rising population figures. The fact that global climate change brings about an increasing demand for water, sparking off conflicts in some regions of the world, is no less important.